The potential of sodium carbonate and Tiron extractions for the determination of silicon contents in plant samples—A method comparison using hydrofluoric acid digestion as reference - Puppe, Daniel; Kaczorek, Danuta; Buhtz, Christian; Schaller, Jörg (Frontiers in Environmental Science, 2023)
For the determination of silicon (Si) concentrations in plant materials several methods are in use. As all of these methods exhibit specific advantages and drawbacks, none of them became prevalent, and thus there is no widely accepted standard protocol for the determination of Si concentrations in plants yet. In our study we performed alkaline (sodium carbonate (Na2CO3) and Tiron) extractions to determine Si concentrations in husk and straw samples of winter wheat (Triticum aestivum). Results obtained from hydrofluoric (HF) acid digestion were used as reference. We evaluated the efficacy of Na2CO3 and Tiron extractions in relation to HF extraction and analyzed the relationships between Si concentrations and phytolith contents in plant samples and plant available Si in corresponding soil samples. Irrespective of the plant material used (husk or straw) we found Tiron to be more efficient in Si extraction compared to Na2CO3. Phytolith contents in plant samples were strongly positively correlated to Si concentrations obtained from extractions, especially in husk samples. Plant available Si in soil samples was also reflected best in husk Si concentrations. Based on our results we recommend establishing the Tiron extraction as standard procedure for the determination of Si concentrations in plant materials in the future.